ANALISIS PERSEDIAAN BAHAN BAKU PADA INDUSTRI TAHU UD MANDIRI DI KELURAHAN WALIAN KECAMATAN TOMOHON SELATAN KOTA TOMOHON (Inventory Analysis of Raw Materials at Tofu Industry â€œUD Mandiriâ€ in Kelurahan Walian, South Tomohon District, Tomohon City) - Ahmad Rizal; Tommy F. Lolowang; Mex L. Sondakh (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2020)
The purposes of this study were to analyze the optimal order of soybean raw materials needed by UD Mandiri per 2018 period, to analyze the total soybean raw material inventory cost of UD Mandiri before and after using the EOQ method, to analyze when the reorder point for soybean raw materials would be carried out by UD Mandiri per period 2018. Data collection in this study was obtained from the interview with the owner of UD Mandiri Tofu Factory. The secondary data were obtained from recorded data available at UD Mandiri tofu factory in 2018. The results of this study showed that the optimal purchase of soybean raw materials for each order according to the EOQ methodÂ in the period 2018 was 16,803 kgÂ with 4 times the purchase of raw materials, so the total quantity of purchases of economical raw materials needed according to the EOQ wasÂ 67,212 kg. Reorder Point according to EOQ was when only 350 kg of inventory left. The total optimal inventory cost according to EOQ was Rp. 52,603,140.Keywords: Raw Material Inventory, EOQ